P 25 CSF biomarkers in CAA compared to AD. (May 2022) - Pfister, M.; Frantsev, R.; Schreiber, F.; Garz, C.; Perosa, V.; Assmann, A.; Düzel, E.; Butryn, M.; Glanz, W.; Vielhaber, S.; Schreiber, S.; John, A.C.
Abstract : Background: Both, cerebral amyloid angiopathy (CAA) and Alzheimer's disease (AD) pathologies coexist on a spectrum, where one end represents parenchymal amyloid deposition causing AD-dementia, and the other end represents vascular amyloid deposition leading to intracerebral hemorrhage and vascular cognitive impairment. CAA is present, to varying degrees, in several AD patients, resulting in a large overlap between the two pathologies in the same brain. Cerebrospinal fluid (CSF) biomarkers could aid in the better discrimination between CAA and AD pathology. Objective: To assess core biomarkers of AD pathology and axonal degeneration in CAA compared to AD and healthy controls. Methods: In a hospital-based setting we recruited 234 patients. N=96 (41%) had probable CAA according to the modified Boston criteria, but did not meet the NIA-AA criteria for AD. N=99 (42%) had AD, and of those n=21 (9%) had AD with CAA, while n=78 (33%) had AD without CAA. N=39 (17%) were considered controls without CAA or AD. CSF measures included β-amyloid (Aβ) 1-40, Aβ 1-42, phosphorylated tau (ptau), total tau (ttau) and neurofilament light chain (NfL). NfL data were missing in n=139 (59%) subjects. Group comparisons were conducted applying ANOVA, adjusted for age and sex, respectively. Bonferroni-adjusted p-values ≤ 0.01 were considered significant. Results: Group differences became obvious for Aβ 1-42, ptau and ttau (Figure). Aβ 1-42 was lower in AD with and without CAA compared to CAA and controls. Ptau was higher in AD with and without CAA compared to CAA and controls. Compared to controls, ttau was higher in AD with and without CAA, and in CAA. There were no group differences for Aβ 1-40 and NfL, albeit there was a clear trend towards higher NfL levels in AD with CAA and CAA compared to AD without CAA and controls (Figure). None of the CSF markers differed between AD with CAA compared to AD without CAA. Conclusion: Lower CSF Aβ 1-42 and higher ptau seem to be specific markers for AD pathology independent of the concurrent occurrence of CAA. They could aid in the discrimination between pure CAA and CAA with AD pathology. Outlook: Upcoming analysis will focus on the correlation between CSF biomarkers and CSVD MRI features according to the STRIVE criteria.